Effects of teachers’ ICT knowledge and utilisation on achievement in secondary school economics in Southwest, Nigeria (2014)
The integration of Information Communication Technology (ICT) into educational practice continues to be lauded as having the potential to dramatically transform the teaching and learning processes. This study investigated the effect of teachers' ICT knowledge and utilization on students’ achievement in Economics in Secondary Schools in Southwest, Nigeria. Multistage sampling technique was used and data were collected from 30 Economics teachers and 360 students in 18 schools from Federal, State and Private secondary schools in Southwest Nigeria. Five research hypotheses and three research instruments guided the study: Economics Achievement test (EAT), Teachers' ICT Knowledge Questionnaire (TIKQ) and Teachers’ ICT Utilisation Questionnaire (TIUQ). Their reliability coefficients were between 0.5 and 0.9 respectively. Data were analysed using Independent T-test and One-way Analysis of Variance (ANOVA). The result revealed that there is no significant difference between teachers level of ICT knowledge on students achievement (t= -0.497, p=0.69); there is no significant difference between students achievement in Economics and teachers ICT utilization (t- 1.05, p—0.53). It however revealed a significant difference between student achievement in Economics and school type (F- 7.55, p=0.001) while it shows that there is no significant difference between Economics achievement of students and teachers gender (t=-0.01; p=0.11). The results thus recommend that constant training workshops, seminars and conferences should be made available by government and school proprietors to teachers in order to improve their teaching skills and use of ICT incorporated resources in their teaching-learning processes in the classroom.